Sustained accumulation of methyl salicylate alters antioxidant protection and reduces tolerance of holm oak to heat stress - Llusia, Joan; Penuelas, Josep; Munné-Bosch, Sergi (Physiologia Plantarum, 2005)
Methyl salicylate (MeSA) is thought to have a major role in biotic and abiotic stresses by acting as a signal to trigger the oxidative burst, which is needed to activate gene expression in plant stress responses. To assess the potential effects of sustained foliar accumulation of MeSA on plant stress tolerance, the extent of photo- and antioxidant protection, lipid peroxidation and visual leaf area damage were evaluated in MeSA-treated (c. 60 nl l−1 in air) and control holm oak (Quercus ilex L.) plants exposed to heat stress. Control plants showed an increase in foliar MeSA levels up to 1.8 nmol [gDW]−1 as temperature increased and they displayed tolerance to temperatures as high as 45°C, which might be attributed, at least in part, to enhanced xanthophyll de-epoxidation and increases in ascorbate and α-tocopherol. MeSA-treated plants showed a sustained foliar accumulation of this compound, with values ranging from 10 to 23 nmol [gDW]−1 throughout the experiment. These plants showed lower ascorbate and tocopherol levels and higher oxidative damage at 50°C than controls, as indicated by enhanced malondialdehyde levels and leaf area damage and lower maximum efficiency of PSII photochemistry (Fv/Fm ratio). These results demonstrate that a sustained foliar accumulation of MeSA is detrimental to plant function and that it can reduce thermotolerance in holm oak by altering antioxidant defences.
The following values have no corresponding Zotero field: publisher: Munksgaard International Publishers
Keywords: antioxidant protection (voyant); foliar MeSA accumulation; heat stress; Holm oak; methyl salicylate